Gender differences in personal characteristics of individuals with different levels and types of perfectionism in the period of early adulthood - Sokolovich Еkaterina А. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
Perfectionism is a distortion of the cognitive structure, which manifests itself in the absence of the ability to objectively evaluate the capabilities of oneself and others. The following techniques were applied in the research: the multidimensional scale of perfectionism P. Hewitt and G. Flett in the adaptation of I. I. Gracheva; Melnikov – Yampolsky psychodiagnostic test. The sample amond 821 persons aged 17 to 28 living in the territory of the Republic of Belarus was taken. It has been discovered that young males and females with different levels and types of perfectionism differ on the severity of their personal characteristics.